The Association Between Diabetes Mellitus and Risk of Sarcopenia: Accumulated Evidences From Observational Studies - Qiao, Yu-Shun; Chai, Yin-He; Gong, Hong-Jian; Zhuldyz, Zhiyessova; Stehouwer, Coen D. A.; Zhou, Jian-Bo; Simó, Rafael (Frontiers in Endocrinology, 2021)
Aim: We performed a meta-analysis of observational studies to evaluate the association between the presence of sarcopenia with HbA1c, prediabetes, diabetes and diabetic complications. Method: The following databases were searched from inception to May 2021 for this meta-analysis: PubMed, Embase, Cochrane and Web of science. We included English language full-text articles that reported the prevalence of sarcopenia in patients with and without diabetes. Quality assessment were performed according to the Newcastle- Ottawa for observational studies. Results: A total of 16 studies were included in this meta-analysis. Three studies showed that high HbA1c levels lead to loss of muscle mass, and one study involving prediabetes showed that people with prediabetes had lower muscle mass, strength, and performance than non-diabetic population. Seven studies showed that people with diabetes had a higher risk of sarcopenia than people without diabetes (combined OR: 2.09, 95% CI:1.62-2.70). Five studies suggested that diabetic complications increased the risk of sarcopenia (combined OR: 2.09 ,95% CI:1.62-2.70). Conclusion: High HbA1c level, prediabetes, diabetes and diabetes complications all significantly were associated with the increased risk of sarcopenia. Therapeutic strategies addressed to avoid the conversion of IGT to diabetes and to optimize the glycemic control seem warranted for preventing or arresting sarcopenia in the diabetic population.,